Dual quantum dot nanobeads-based fluorescence-linked immunosorbent assay for simultaneous detection of aflatoxin B1 and zearalenone in feedstuffs. (1st January 2022) - Li, Runxian; Wen, Yang; Yang, Luqing; Liu, Anguo; Wang, Fenglai; He, Pingli
Highlights: Dual quantum dot nanobeads were applied in fluorescence-linked immunosorbent assay (QBs-FLISA). Two target mycotoxins can be detected simultaneously by QBs-FLISA. Compared with ELISA, detection sensitivity of QBs-FLISA was increased and detection duration was decreased. QBs-FLISA was successfully applied in feedstuff analysis. Abstract: A novel dual quantum dot nanobeads-based fluorescence-linked immunosorbent assay (QBs-FLISA) was successfully developed for simultaneously detecting aflatoxin B1 (AFB1) and zearalenone (ZEN) in feedstuffs. Dual CdSe/ZnS quantum dot nanobeads with different diameters that emit red and green fluorescence were conjugated with anti-AFB1 and anti-ZEN monoclonal antibodies to prepare fluorescent probes, which greatly enhance analytical performance. Under the optimal conditions, the limits of detection for AFB1 and ZEN were 9.3 and 102.1 pg mL −1, respectively. The recoveries ranged from 82.50% to 116.21% with relative standard deviation less than 11.3%. Compared with traditional enzyme-linked immunosorbent assay, detection sensitivities of AFB1 and ZEN using QBs-FLISA were increased 20 and 5 folds, respectively. In addition, results of feedstuff samples analyzed by QBs-FLISA and liquid chromatography tandem mass spectrometry showed a good agreement (R 2 = 0.99).